2020
DOI: 10.1002/lipd.12252
|View full text |Cite
|
Sign up to set email alerts
|

Docosahexaenoic Acid Incorporation Is Not Affected by Doxorubicin Chemotherapy in either Whole Cell or Lipid Raft Phospholipids of Breast Cancer Cells in vitro and Tumor Phospholipids in vivo

Abstract: To better understand how docosahexaenoic acid (DHA) improves the effects of doxorubicin (DOX), we examined DHA AE DOX on changes in whole cell and lipid raft phospholipids (PL) of MDA-MB-231 and MCF-7 breast cancer cells. We sought to confirm whether the relative changes in PL DHA content of MDA-MB-231 cells could be extended to PL from MDA-MB-231 tumors grown in mice fed a DHA supplemented diet AEDOX. Treatment with DHA did not change PL composition yet DOX increased the proportion of phosphatidylserine in MC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(35 citation statements)
references
References 61 publications
(102 reference statements)
1
33
1
Order By: Relevance
“…In contrast, Achkar et al in 2020 found a general downregulation of most metabolites and lipids (including etherPEs with PUFAs) in egg-developed tumors (MDA-MB-231) treated with DOX 31 . This finding is in apparent contradiction to our results and those reported by Newel et al in 2020 30 . Nevertheless, the study of Achkar et al in 2020 about DOX-treated solid tumors contained alive, damaged, and dead cell debris 31 .…”
Section: Comparison With Other Lipidomics Studiescontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast, Achkar et al in 2020 found a general downregulation of most metabolites and lipids (including etherPEs with PUFAs) in egg-developed tumors (MDA-MB-231) treated with DOX 31 . This finding is in apparent contradiction to our results and those reported by Newel et al in 2020 30 . Nevertheless, the study of Achkar et al in 2020 about DOX-treated solid tumors contained alive, damaged, and dead cell debris 31 .…”
Section: Comparison With Other Lipidomics Studiescontrasting
confidence: 99%
“…We did not observe a general change of lipids in HepG2 and Huh7, except for the increase of PUFAs, etherPEs with PUFAs, and PGs (Figure 3). This observation agrees with the recent study by Newell et al in 2020, which does not report strong changes in the lipid families in breast cancer cells (MDA-MB-231 and MCF-7) treated with DOX in combination with fatty acids 30 . They did not include etherPEs nor PGs in their study, so, as new result, we observed that both anthracyclins upregulated these families of glycerophospholipids in HepG2 and Huh7 (PUFAs and etherPEs with PUFAs increased in SNU449 as well, Figure 3).…”
Section: Comparison With Other Lipidomics Studiessupporting
confidence: 94%
See 2 more Smart Citations
“…It is known that PUFAs potentiate the effect of DOX in vitro and in animal models [ 69 , 70 ]. This effect might be general, as it would potentiate the lipid peroxidation in ferroptosis induced by anthracyclins.…”
Section: Discussionmentioning
confidence: 99%